Immunosuppressive therapy withdrawal after remission achievement in patients with lupus nephritis. (28th April 2021) - Zen, Margherita; Fuzzi, Enrico; Loredo Martinez, Marta; Depascale, Roberto; Fredi, Micaela; Gatto, Mariele; Larosa, Maddalena; Saccon, Francesca; Iaccarino, Luca; Doria, Andrea
Abstract: Objectives: Whether immunosuppressive therapy may be safely withdrawn in lupus nephritis (LN) is still unclear. We assessed rate and predictors of flare after IS withdrawal in patients with LN in remission. Methods: Patients with biopsy-proven LN treated with immunosuppressants (IS) between 1980 and 2020 were considered. Remission was defined as normal serum creatinine, proteinuria <0.5 g/24 h, inactive urine sediment, and no extra-renal SLE activity on stable immunosuppressive and/or antimalarial therapy and/or prednisone ≤5mg/day. IS discontinuation was defined as the complete withdrawal of immunosuppressive therapy, flares according to SLEDAI Flare Index. Predictors of flare were analysed by multivariate logistic regression analysis. Results: Among 513 SLE patients included in our database, 270 had LN. Of them, 238 underwent renal biopsy and were treated with IS. Eighty-three patients (34.8%) discontinued IS, 46 (30) months after remission achievement. During a mean (s .d .) follow-up of 116.5 (78) months, 19 patients (22.9%) developed a flare (8/19 renal) and were re-treated; 14/19 (73.7%) re-achieved remission after restarting therapy. Patients treated with IS therapy for at least 3 years after remission achievement had the lowest risk of relapse (OR 0.284, 95% CI: 0.093, 0.867; P = 0.023). At multivariate analysis, antimalarial maintenance therapy (OR 0.194, 95% CI: 0.038, 0.978; P = 0.047), age at IS discontinuation (OR 0.93, 95% CI: 0.868, 0.997; P = 0.040), remission duration >3 years before IS discontinuation (OR 0.231, 95% CI: 0.058, 0.920; P = 0.038) were protective against disease flares. Conclusions: Withdrawal of IS is feasible in LN patients in remission for at least 3 years and on antimalarial therapy. Patients who experience flares can re-achieve remission with an appropriate treatment.